2012
DOI: 10.1038/srep00741
|View full text |Cite
|
Sign up to set email alerts
|

Cold Radiofrequency Plasma Treatment Modifies Wettability and Germination Speed of Plant Seeds

Abstract: We report the possibility to modify the wetting properties of the surfaces of a diversity of seeds including: lentils (Lens culinaris), beans (Phaseolus vulgaris) and wheat (Triticum, species C9) by cold radiofrequency air plasma treatment. Air plasma treatment leads to the dramatic decrease in the apparent contact angle. Moreover, the speed of germination and yield (germination rate) of seeds can be modified by preliminary plasma treatment. The change in the wetting properties of seeds is at least partially d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
227
5
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 282 publications
(270 citation statements)
references
References 37 publications
27
227
5
1
Order By: Relevance
“…Our previous report Nishioka et al, 2014 indicated that the low-pressure plasma treatment under the same conditions as this study did not have significant negative effects on germination rates of brassicaceous seeds B. campestris var. amplexicaulis , and other studies have reported that plasma treatment of seeds improves their germination and sprouting process Bormashenko et al, 2012;Dhayal et al, 2006 . In this study, it was found that low-pressure plasma treatment could inactivate the important seed-borne plant pathogenic bacterium, X. campestris on seeds and damaged the bacterial cell membrane and biomolecules, such as DNA, inside the cells. The low-pressure gas plasma system will be a useful and nonchemical seed disinfection method in the future.…”
Section: Food Security Nato Sicence For Peace and Security Seriesmentioning
confidence: 64%
“…Our previous report Nishioka et al, 2014 indicated that the low-pressure plasma treatment under the same conditions as this study did not have significant negative effects on germination rates of brassicaceous seeds B. campestris var. amplexicaulis , and other studies have reported that plasma treatment of seeds improves their germination and sprouting process Bormashenko et al, 2012;Dhayal et al, 2006 . In this study, it was found that low-pressure plasma treatment could inactivate the important seed-borne plant pathogenic bacterium, X. campestris on seeds and damaged the bacterial cell membrane and biomolecules, such as DNA, inside the cells. The low-pressure gas plasma system will be a useful and nonchemical seed disinfection method in the future.…”
Section: Food Security Nato Sicence For Peace and Security Seriesmentioning
confidence: 64%
“…This result agreed with the findings of Bormashenko et al . who reported that cold radiofrequency air plasma treatment plasma could improve the water uptake of oat and wheat seeds23. Seeds immersed into cold plasma are subjected to an attack by oxygen radicals and are bombarded by ions resulting in seed coat erosion and etched/eroded surfaces24.…”
Section: Discussionmentioning
confidence: 99%
“…A requirement for this behaviour is that the solid surface be chemically heterogeneous so as to allow different distributions of chemical functional groups between those that are on the surface and those buried deeper in it. This effect is associated with a variety of phenomena including the marked differences between chemisorbed and physisorbed monolayers 7 and wetting transitions 8 with implications ranging from plant growth 9 through electrovariable optical components 10 to nanofiber membranes 11 , which are chemically heterogeneous.…”
mentioning
confidence: 99%